[factoring part 2][section 41]

(1.)  7x + 7y              here is the problem

=    7(x + y)               factor

result: 7(x + y)

(2.)   3a + 9b              here is the problem

=    3(a + 3b)              factor

result:  3(a + 3b)

(3.)  8x - 4y                 here is the problem

=    4(2x - y)                factor

result:  4(2x - y)

(4.)   ax + bx                  here is the problem

=      x(a + b)               factor

result:  x(a + b)

(5.)  3x - awx                here is the problem

=    x(3 - aw)                factor

result:  x(3 - aw)

(6.)  4c + ac + bc            here is the problem

=     c(4 + a + b)            factor

result:  c(4 + a + b)

(7.)  ay + by + 3y             here is the problem

=     y(a + b + 3)             factor

result:  y(a + b + 3)

(8.)  d2 + 2d + ad             here is the problem

=   d(d + 2 + a)              factor

result:  d(d + 2 + a)

(9.)  5t + 10t2 + t3                here is the problem

=     t(5 + 10t + t2)              factor

result:  t(5 + 10t + t2)

(10.)   cdh3 + c2dh + c3d2h2       here is the problem

=   cdh(h2 + c + c2dh)           factor

result:  cdh(h2 + c + c2dh)